Extended endonasal approach versus maxillary swing approach to the parapharyngeal space. Issue 6 (31st January 2018) - Roger, Vivien; Patron, Vincent; Moreau, Sylvain; Kanagalingam, Jeeve; Babin, Emmanuel; Hitier, Martin
Abstract: Background: The nasopharyngeal and parapharyngeal spaces are difficult for surgeons to access. Of the various external routes described, the maxillary swing has emerged as the gold standard because of its simplicity. However, its morbidity has led to the development of less invasive techniques. The purpose of our study was to compare the surgical anatomy of the maxillary swing with that of the endoscopic endonasal approach. Methods: Each procedure was performed on 10 anatomic specimens. The exposure and the limits obtained were evaluated. A CT scan analysis was performed. Results: The endoscopic endonasal approach extended the limits, offering wider exposure. The endoscopic endonasal approach made possible better visualization of deep structures and precise dissection of the parapharyngeal spaces. However, the maxillary swing provided better access to the oropharynx and could be completed 3 times faster. Conclusion: The endoscopic endonasal approach provides excellent exposure, a wide dissection range, and precise definition of anatomic structures, making it an alternative of choice rather than the maxillary swing approach.